Primary neuroendocrine tumor of the liver - Galarreta, Lucia F. (2024)
Neuroendocrine tumors generally originate in the digestive tract or pancreas, developing liver metastases throughout their evolution. The presence of a primary neuroendocrine tumor of the liver is still controversial and there are very few cases. We present a case of a primary neuroendocrine tumor of the liver confirmed by anatomo-pathological study and images. The patient underwent two major liver resections, lastly preserving only segment IV.